2011
DOI: 10.7326/0003-4819-155-5-201109060-00354
|View full text |Cite
|
Sign up to set email alerts
|

“July Effect”: Impact of the Academic Year-End Changeover on Patient Outcomes

Abstract: National Heart, Lung, and Blood Institute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
220
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(227 citation statements)
references
References 63 publications
4
220
2
1
Order By: Relevance
“…The existence of the "July effect" (whereby medical trainees beginning new clinical roles affect medical error rates, patient outcomes, and departmental productivity) remains uncertain in the literature. 19 Third, in the post-implementation group, a substantial proportion of patient data was excluded, mostly due to clerical and administrative data error. It is impossible to determine what impact this may have had on the results.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The existence of the "July effect" (whereby medical trainees beginning new clinical roles affect medical error rates, patient outcomes, and departmental productivity) remains uncertain in the literature. 19 Third, in the post-implementation group, a substantial proportion of patient data was excluded, mostly due to clerical and administrative data error. It is impossible to determine what impact this may have had on the results.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…A recent systematic review supported the existence of a ''July effect'' with a higher incidence of errors and adverse events in the early months of the academic year, particularly in studies with higher-quality designs and larger samples. 64 Studies that have explored the effect of transitions in anesthesiology across the educational continuum are relatively rare, although an Australian study found that the adjusted risk for adverse events from care provided by anesthesiology residents was significantly higher at the start of the academic year. 65 Also, a study in the United States showed that more than one-half of anesthesiology residents failed to adhere to the standard of care for preoperative cardiac evaluation.…”
Section: Transitions Across the Medical Education Continuummentioning
confidence: 99%
“…The individual nuances of working in specific departments are left out due to issues of generalisability and time constraints. The lack of familiarity with location and staff in addition to the lack of information and guidance regarding proper documentation, ordering and sending lab tests, and so on leaves residents unacceptably overwhelmed and unprepared to handle their duties, when they start work [3]. Interns are an integral part of healthcare delivery – they work closely with patients and other members of the healthcare delivery team.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate training of interns regarding proper documentation is an integral part of the safe and efficient care of patients and is closely related to hospital compliance with regulations and thus hospital reimbursement. The time period corresponding to the beginning of residency training in July is associated with reduced quality of healthcare delivery and patient outcomes [3]. This reduction in quality is well known and documented in the medical literature and is known collectively as the ‘July Effect’ [49].…”
Section: Introductionmentioning
confidence: 99%